Retrodunal dry grassland vegetation in the hinterland of Velika Plaža (Montenegro) - Stesevic, Danijela; Stanišić-Vujačić, Milica; Milanović, Đorđije; Šilc, Urban (Acta Botanica Croatica, 2025)
The article presents the results of a study on retrodunal dry grassland communities in the hinterland of Velika Plaža (town of Ulcinj, Montenegro). They are documented with 47 relevés, which were compared with 177 dry grassland and 107 sand dune vegetation plots. Using hierarchical cluster analysis (flexible Beta method), and ordination (non-metric multidimensional scaling), the dry grasslands from the hinterland of Velika Plaža were grouped into three clusters, representing three new associations: Junco bufonii-Vulpietum ligusticae, Tuberario guttatae-Avellinietum festucoidis, Helinathemo jonii-Artemisietum campestris. The first association develops at the transition from wet grassland on gleyic soil to xerophilous grassland over sands. It is characterized by relatively high biomass production and is thus regularly mowed. The second association develops on somewhat higher and better drained sands, and due to very low biomass production, it is used exclusively as pasture. The Helinathemo jonii-Artemisietum campestris is also a pasture, evolved as a result of progressive natural succession of dune sands on the highest part of the dune system. It is represented by two sub-associations, one of which is characterized by the extremely high coverage of Asphodelus ramosus. Stands with A. ramosus primarily grow in the form of narrow strips along roads and around fences, sheltered from the wind, and on more developed and humus-rich soils. This suggests that Asphodeletosum ramosi present the terminal stage of the dune community Helianthemo jonii-Artemisietum campestris. The latter association is classified within the Crucianellion maritimae (Ammophiletea arundinaceae), whereas the other two belong to the Vulpio-Lotion (Helianthemetea guttati).